Pengaruh Asosiasi Merek, Loyalitas Merek, Kesadaran Merek dan Citra Merek terhadap Ekuitas Merek Nike Di Media Sosial Pada Kalangan Konsumen Muda - Ristanto Wahyu Nugroho; Salman Faris Insani; Bambang Nur Cahyaningrum (Universitas Veteran Bangun Nusantara, 2020)
The purpose of this research is to test and analyze the influence of brand associations, brand loyalty, brand awareness and brand image on brand equity on young consumers. The samples in this study were 137 students of the University of Veteran Bangun Nusantara, University of Sebelas Maret Surakarta and University of Muhammadiyah Surakarta. The sampling method used in this study is nonprobability sampling, while the technique used is purposive sampling. The results of data from 137 respondents were analyzed using descriptive statistical testing and multiple linear regression using the Stastitular Package for Social Science Computer Progamme (SPSS) version 21. Results through multiple linear regression analyses, showed that brand associations and brand loyalty had an effect on Nike brand equity on social media among young consumers while brand awareness and brand image, had no effect on Nike brand equities on social media among young consumers. Keywords: brand associations, brand loyalty, brand awareness